Motivation Analysis of Students Selecting Al-Kinanah Jambi Islamic Boarding School as an Arabic Learning Institution - Rita; Mohamad Muspawi; Sahrizal Vahlepi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2021)
Abstract: This thesis discusses the Analysis of Students' Motivation for Choosing Pesantren Al-Kinanah Jambi as an Arabic Language Learning Institution. With the problem of how students can be motivated to choose Al-Kinanah Jambi Islamic boarding school as an Arabic language learning institution, what are the factors that encourage students to choose Jambi's Al-Kinanah Islamic Boarding School as an Arabic language learning institution. This type of research is qualitative research, namely data obtained in the form of opinions, views or other expressions of thought obtained through interviews. While the method used is observation (observation), interviews, and documentation. While the sources of data in this study were obtained from the leadership of the Al-Kinanah Islamic Boarding School Jambi, TU staff and students. He made it as the object of the informant because the researcher said that they are competent to provide information or data that is closely related to the problem under study. Data was collected using observation, interviews and documentation. The data analysis used is qualitative data analysis. Based on the results of this study, it shows that there are two factors that motivate students to choose Pesantren Al-Kinanah Jambi as an Arabic language learning institution (1) internal factors, namely factors that come from within the student without any coercion from others. From the results of interviews conducted by researchers with students at the Al-Kinanah Islamic Boarding School in Jambi, almost some of the students said that they chose to enter the pesantren of their own volition and not coercion from others. They think that by going to boarding school this will make them a better person, and they think that this Islamic boarding school has good religious knowledge and fun learning because they not only study religion but they can also learn general lessons such as science lessons, social studies and so on. (2) external factors, namely factors that come not from themselves but from input and encouragement from parents. From the results of interviews conducted by researchers to Al-Kinanah Jambi Islamic boarding school students, most of the students chose to enter the pesantren because of encouragement from their parents. With the aim of parents so that they can become children with noble character and there are those who supervise the activities they do during the Islamic boarding school. From the results of research conducted on April 15, 2021, the authors conclude that the motivation of students to choose the Al-Kinanah Jambi Islamic boarding school consists of two factors, namely internal factors and external factors. Internal factors are factors that come from within the students who wish to continue their education at the Al-Kinanah Jambi Islamic boarding school, with the aim of improving themselves and learning foreign languages ​​in the pesantren, namely English and Arabic. While external factors are factors that come from the encouragement and input of the family with the aim that their children can get good religious and moral education in the Al-Kinana Jambi Islamic boarding school.